Scientometric Assessment of Publication Productivity of JNTBGRI, Thiruvananthapuram - B. Mini Devi and Lekshmi V (DESIDOC Journal of Library & Information Technology, 2014)
The article explores the scientometric assessment of publication productivity of Jawaharlal Nehru Tropical Botanic Garden and Research Institute (JNTBGRI). The data for the study was taken from the Annual report of the JNTBGRI from 2001-2010 which were then tabulated and analysed. The scientists of JNTBGRI prefer mostly Indian journals to publish their articles. Journal of Economic Taxonomic Botany tops the list with the highest number of articles 50 (9.11 %), followed by Zoos (Print Journal) with 39 articles. India is the leading country with 54.67 % of total journals. The collaboration coefficient of journal article during the year 2010 is found to be 0.7541. The articles published in the journal Current Science got 45 citations and Journal of Ethnopharmacology got only 5 citations. The article tries to analyse the country-wise distribution of journals, collaboration-coefficient in research and subject areas in which research has been done